Pengembangan Pembudayaan Agama Islam Berbasis Kegiatan Keagamaan di Sekolah - Silvia Indah Lestari; Aliqma Mutiara Zamil; Agus Joko Purwanto (Jurnal Wahana Literasi Pendidikan, 2026)
His research is motivated by the importance of transforming Islamic Religious Education (PAI) from mere cognitive teaching toward the internalization of religious values through religious culturing within the school environment. The main focus of this study is to analyze the development of Islamic religious culture based on religious activities as an instrument for student character building. The research method used is a qualitative approach with a library research type. Data were collected through documentation techniques sourced from relevant literature, official documents, and observation results related to religious activities at Madrasah Aliyah Al-Mubarok, Central Lampung. The research results indicate that the development of religious culture is carried out through the integration of spiritual values into the school ecosystem through three main stages: formulation, implementation, and evaluation. The implementation of religious activities that serve as pillars of culturing includes the habituation of Dhuha prayer to train discipline and focus (khusyu'), the implementation of khotmil Qur'an through the bil ghoib and binnadzor methods, congregational Dzuhur prayer to build social cohesion, and the celebration of Islamic Great Days (PHBI) as a means of strengthening religious identity. Active student participation is encouraged by internal motivation and external support from the school environment. This research concludes that routine and sustainable programmed religious activities are effective in transforming Islamic values into student behavior and character in daily life.